New Ideas for digital affordability: Is a paradigm shift possible? - Goggin, Gerard (Journal of Telecommunications and the Digital Economy, 2014)
Affordability is an important and recurrent issue in telecommunications and the digital economy. With the rise of the Internet and mobiles, there have emerged a range of new ideas about addressing long-standing affordability issues. Yet it has been difficult for the interested policy actors to forge such ideas into a new paradigm, and even harder to gain a new consensus and public support. Accordingly, this paper considers this policy impasse, analyses leading directions, and argues for the importance of arriving at a new carefully coordinated and unified approach to affordability.